Determination and classification of stress level using EEG signal and audio modalities - Syahrull Hi-FI Syam Ahmad Jamil (School of Mechatronic Engineering, 2011)
This research work intends to determine the stress level (normal, very low stress, low stress, very moderate stress, moderate stress, high stress and very high stress) at 3 different sound pressure levels (60 dB, 70 dB and 80 dB) through physiological signal measurement which is Electroencephalogram signal (EEG).